Trends in colonoscopy and fecal occult blood test use after the introduction of dual screening offers in Germany: results from a large population-based study, 2003-2016 - Chen, Chen; Stock, Christian; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (Preventive medicine, 2019)
An increasing number of countries have recently introduced colorectal cancer (CRC) screening programs. Typically, one specific screening exam, such as fecal occult blood test (FOBT) or flexible sigmoidoscopy, is offered as a primary screening test. We aimed to assess trends in FOBT and colonoscopy use in Germany following the introduction of the offer of screening colonoscopy as an alternative to FOBT in 2002. We used data from 4052 control participants aged 50-79years recruited during 2003-2016 for a population-based case-control study in Germany. Prevalence of FOBT and colonoscopy lifetime and recent use was analyzed and trends over time were examined. The percentage of all respondents who had ever undergone a colonoscopy (for either screening or diagnostic purpose) increased markedly over time from 44.6% in 2003-2005 to 57.5% in 2013-2016 (p<0.0001). Large increases were also observed for colonoscopy use within 10years (from 38.0% to 52.8%, p<0.0001), whereas FOBT uptake within one to two years declined from 54.0% to 33.3%. By 2013-2016, 67.2% of respondents either had an FOBT within one to two years or a colonoscopy within 10years, and this percentage had remained relatively stable over time. This study demonstrates a large increase in colonoscopy utilization since colonoscopy was included as an alternative primary screening test, which was accompanied by a substantial decline in FOBT use. Although the overall adherence to CRC screening recommendations remained stable, the substantial shift of share from FOBT to colonoscopy is expected to yield more protection against CRC incidence and mortality.
Gesehen am 03.06.2019